Morphological, Physiological and Proteomic Analyses Provide Insights into the Improvement of Castor Bean Productivity of a Dwarf Variety in Comparing with a High-Stalk Variety - Hu, Wenjun; Chen, Lin; Qiu, Xiaoyun; Lu, Hongling; Wei, Jia; Bai, Yueqing; He, Ningjia; Hu, Rongbin; Sun, Li; Zhang, Hong; Shen, Guoxin (Frontiers in Plant Science, 2016)
Ricinus communis displays a broad range of phenotypic diversity in size, with dwarf, common, and large-sized varieties. To better understand the differences in plant productivity between a high-stalk variety and a dwarf variety under normal growth conditions, we carried out a comparative proteomic study between Zhebi 100 (a high stalk variety) and Zhebi 26 (a dwarf variety) combined with agronomic and physiological analyses. Over 1000 proteins were detected, 38 of which differed significantly between the two varieties and were identified by mass spectrometry. Compared with Zhebi 100, we found that photosynthesis, energy, and protein biosynthesis related proteins decreased in abundance in Zhebi 26. The lower yield of the dwarf castor is likely related to its lower photosynthetic rate, therefore we hypothesize that the lower yield of the dwarf castor, in comparing to high stalk castor, could be increased by increasing planting density. Consequently, we demonstrated that at the higher planting density in Zhebi 26 (36,000 seedlings/hm²) can achieve a higher yield than that of Zhebi 100 (12,000 seedlings/hm²). Proteomic and physiological studies showed that for developing dwarf R. communis cultivar that is suitable for large scale-production (i.e. mechanical harvesting), it is imperative to identify the optimum planting density that will contribute to higher leaf area index, higher photosynthesis, and eventually higher productivity.